An Overview of Indian Culinary Journey with Glimpse of Regional Cuisine - Anusua Ghosh (Bulletin of Culinary Art and Hospitality, 2022)
With diversity in race, religion, culture, and language, Indian cuisine is unique to each region. The varied nature of the cuisine is mainly based on what is grown and harvested, depending on the climate and region. Various spices and herbs are added to enhance the flavor and to keep the food fresh. Moreover, spices and herbs are also used for medicinal purposes. History suggests that earlier people consumed traditional food and followed the dietary rules outlined in Ayurveda. In Ayurveda, food and wellbeing are highly related, with nutrition plays as a central role in ensuring a balance of the mind, body, and spirit. The influence of various invaders and traders such as the Greeks, Mughals, Mongols, the Chinese, British, and the Portuguese at different phases in time have immensely contributed to enriching and transforming the food culture of India. This article presents an overview of the Indian culinary journey with emphasis on regional cuisine from the northern to the southern and western to the eastern part of the sub-continent.